Investigating the semantic development of modal markers - Potočnik, Tomaž (Clotho, 2019)
The article tackles the problem of studying diachronic semantic changes of modal markers in Latin. It proposes to do so by using context as a proxy for tracing the development of otherwise unchanging forms. In the first part, the leading theoretical positions in modality studies are presented, especially the notions of deontic modality, epistemic modality, and pathways of modality. In the second part, Heine's model for studying the role of context in language change is presented and applied to the modal verb licet . In the case study of licet, an attempt is made to identify the so-called switch context, which co-creates the conditions necessary for the semantic change.
Keywords: jezikoslovje; latinščina; modalnost; semantika